An Overview Aloe Vera Compresses to Reduce A Child's Body Temperature in Dengue Hemorrhagic Fever nn The Emergency Department - Putri, I Dewa Ayu Nanda Arisma; Sanjana, I Wayan Edi; Sukadana, I Gede (Babali Emergency and Disaster Research, 2024)
Background: Hyperthermia or high fever is a condition characterized by an increase in body temperature beyond normal limits. Fever will occur if a person's health condition is disturbed. Body temperature is said to be within normal limits if it is in the range of 36,5-37,50C. Research Objective: To determine the results of giving aloe vera compresses to reduce children's body temperature in hyperthermia with Dengue haemorrhagic fever in the Emergency Room of Klungkung Hospital. Methods: A Case study method using in this research. Two sample are chosen using Purposive sampling technique. Providing nursing interventions in the form of aloe vera compresses to reduce children's body temperature with hyperthermia in dengue haemorrhagic fever. Results: The first patient had a body temperature of 38.9 C before intervention and a body temperature of 37,5oC after intervention. The second patient had a body temperature of 38oC before intervention and a body temperature of 37,9oC after intervention. Conclusions: After being given an intervention in the form of aloe vera compresses proved effective in reducing fever in children.